A Primer for Developing Measures of Science Content Knowledge for Small-Scale Research and Instructional Use - Bass, Kristin M. (CBE Life Sci Educ, 2016)
The credibility of conclusions made about the effectiveness of educational interventions depends greatly on the quality of the assessments used to measure learning gains. This essay, intended for faculty involved in small-scale projects, courses, or educational research, provides a step-by-step guide to the process of developing, scoring, and validating high-quality content knowledge assessments. We illustrate our discussion with examples from our assessments of high school students’ understanding of concepts in cell biology and epigenetics. Throughout, we emphasize the iterative nature of the development process, the importance of creating instruments aligned to the learning goals of an intervention or curricula, and the importance of collaborating with other content and measurement specialists along the way.